2020
DOI: 10.1177/0018720820966082
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of an Innovative Exercise to Relieve Chronic Low Back Pain in Sedentary Workers

Abstract: Objective The purpose of the study was to examine the effectiveness of a novel supported dynamic lumbar extension with the abdominal drawing-in maneuver (ADIM) technique on stature change, deep abdominal muscle activity, trunk muscle fatigue, and pain intensity during prolonged sitting in chronic low back pain (CLBP) participants. Background Prolonged sitting can cause trunk muscle fatigue from continuous contraction of deep trunk muscles in seated postures. Deficiency of activity of deep muscles can reduce mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Stature change response has been used to reflect the influence of daily routine work; through measurement at certain times of day on the same day [23,33,34], and between consecutive days [24,35,36]. However, it is difficult to interpret whether the stature change response recorded is truly due to the function of previous loading history or to the natural fluctuation of stature change response between days.…”
Section: Introductionmentioning
confidence: 99%
“…Stature change response has been used to reflect the influence of daily routine work; through measurement at certain times of day on the same day [23,33,34], and between consecutive days [24,35,36]. However, it is difficult to interpret whether the stature change response recorded is truly due to the function of previous loading history or to the natural fluctuation of stature change response between days.…”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of the deep trunk muscle is thought to raise intra-abdominal pressure [59], resulting in decreased spinal loading [60,61]. This suggests that the CSE with the ADIM technique can increase deep trunk muscle activity in CLBP participants by reducing compression forces on the spine during prolonged sitting [8], leading to improved stature recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Deep trunk muscle fatigue may arise from continuous contraction of the trunk muscles during prolonged sitting [8][9][10]. This fatigue reduces muscular support to the spine and increases stress on ligaments and intervertebral discs [9,10]; consequently, it reduces intervertebral disc height [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Low-back pain is strongly associated with a sedentary lifestyle [7]; specifically, a more sedentary lifestyle is an independent risk factor for musculoskeletal disorders [8]. Further, a sedentary lifestyle is a risk factor for low-back pain since it can cause muscle fatigue, due to continued core muscle contractions, increased intradiscal loads, and the weakening of the posterior lumbar structure [9,10]. Kett et al [8,11] reported increased lumbar muscle stiffness, as measured by an indentometer, after 4.5 h of sedentary work.…”
Section: Introductionmentioning
confidence: 99%